International Legal Mechanisms for Protecting Digital Identity in Cross-Border Legal Relations - Artyshuk-Bereziuk, Larysa (Український політико-правовий дискурс, 2024)
The relevance of this study is determined by the rapid digitalization of cross-border legal relations and the growing need to ensure effective international legal protection of digital identity in the context of increasing transnational data flows and technological transformations. The purpose of this article is to substantiate the theoretical and legal foundations and to identify the distinctive features of the functioning and development of international legal mechanisms for the protection of digital identity in cross-border legal relations. The study employed methods of scholarly literature analysis to ascertain the current state of research on the legal regulation of decentralized digital identification systems and the conceptualization of digital sovereignty, as well as methods of synthesis, generalization, and systematization to integrate doctrinal and normative approaches, structure digital identification models, identify the principal legal challenges, and formulate substantiated conclusions regarding the improvement of the legal framework. The study established that digital identity has acquired a complex legal nature, combining elements of personal data, electronic identification, and informational self-determination, which necessitates the formation of comprehensive international legal mechanisms for its protection. The existing international standards and principles governing the protection of personal data and digital identity were analyzed, along with the role of major international organizations, in particular the United Nations and the Council of Europe, in shaping a unified regulatory approach. The distinctive features of the European legal framework were examined, including the impact of the General Data Protection Regulation and the eIDAS Regulation on ensuring the cross-border recognition of electronic identification and trust services. It was determined that contemporary international legal mechanisms have attained a high level of normative development yet remain fragmented and insufficiently harmonized at the global level. Particular attention was devoted to the analysis of legal challenges related to jurisdiction, applicable law, and the distribution of responsibility among participants in transnational digital interactions. It was established that technological innovations, in particular artificial intelligence and decentralized digital identification models, significantly influence the transformation of legal regulation, creating both new opportunities and risks for the protection of individual rights. The conclusions indicate that the effectiveness of international legal mechanisms for the protection of digital identity depends on the level of coordination among national legal systems, the development of interoperable standards, and the strengthening of international cooperation. It was demonstrated that the further improvement of these mechanisms requires the harmonization of legal norms, the expansion of mutual recognition instruments, and the formation of flexible, technologically neutral regulatory approaches capable of ensuring a high level of digital identity protection in the global digital space.